MQTT live performance on the INA-CBT communication system: a measurement-based evaluation - Kusuma, A. A. N. Ananda; Agastani, Tahar; Giyana, Rifqi F.; Anggraeni, Sakinah P.; Hartawan, Arfan R.; Palokoto, Toto B.; Pinastiko, Widrianto S. (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Cable-based tsunameters have been deployed in Indonesia under the name of the INA-CBT project. Currently, the system operated at the Labuan Bajo landing station works well and sends aggregated data from the seafloor sensors to a central or read down station in Jakarta for further processing. The current scheme makes use of a publish and subscribe indirect communication among the landing station (LS) as the publisher and various clients as subscribers for the sensor data. Message queue telemetry transport (MQTT) was selected as the application-layer protocol for implementing this communication scheme. This paper presents a measurement-based evaluation of the MQTT live performance by observing the MQTT messages’ latencies received at the subscriber of the INA-CBT’s MQTT broker. The results give insight on the general achievable performance of the INA-CBT communication system in providing reliable data for the tsunami detection system. Furthermore, the results obtained can be used as communication parameters for making a more realistic virtual testbed for designing a more appropriate and scalable CBT system.